BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PSN (3M PLUS)SEBAGAI UPAYA PENCEGAHAN DBD PADA MASYARAKAT KELURAHAN SENDANGMULYO, SEMARANG - Tri Nurul Azizah; Zahroh Shaluhiyah; Syamsulhuda BM (Jurnal Kesehatan Masyarakat (Undip), 2017)
Dengue fever, Dengue (DBD) is a disease of acute fibrils found first occurred in the year 1780 simultaneously in Asia, Africa, and North America. Dengue Fever Disease is still one of the major public health problems in Indonesia. The number of sufferers and area distribution growing with increasing mobility and population density. Mosquito Nest eradication (PSN) is the effort eradicating dengue fever, Dengue (DBD) through the control of vector. Benchmark the success of Mosquito Nest Eradication activities (PSN) that is based on the number of free Larva (ABJ) according to Regulation No 581 in 1992. The purpose of this research was to analyze several factors related to the behavior of the Mosquito Nest Eradication (PSN) 3Mplus in Sendangmulyo, Semarang. This type of research with cross-sectional study. The respondents of the study amounted to 90 people. Data collection through interviews using a questionnaire. Statistical tests were used to analyze the relationships between variables using the Chi-Square. The results showed 56.7% of respondents included categories that have good behavior, 48.3% of respondents say the giving of information by cadres are already good, 66.7% of respondents say the existence of rules or policies are applied, 66.7% of respondents said family support is already good, 66.7% of respondents say the support of community leaders is already good. There is a relationship between regulations or existing policy (p = 0.044), knowledge of the respondents (p = 0.017), family support (p = 0.024), and the support of community leaders (p = 0.024). There is a meaningful relationship between the existing rules or policies, family support, knowledge of the respondents, and support community leaders with the behavior of the Mosquito Nest Eradication (PSN) 3Mplus as Dengue prevention efforts Dengue (DBD) in Sendangmulyo Village, Semarang community.